The Direct Influence of Organizational Culture on Employee Work Productivity at the Office of the Ministry of Religious Affairs, West Sumatra Province - ., Joben; Gistituati, Nurhizrah; ., Yahya; ., Irsyad; ., Nellitawati (Journal of Ecohumanism, 2025)
This study aims to examine the direct influence of organizational culture on employee productivity at the Ministry of Religious Affairs in West Sumatra. The research employs a descriptive quantitative method, with the sample determined using stratified proportional random sampling based on the Slovin formula, resulting in 382 employees from the West Sumatra Provincial Office of the Ministry of Religious Affairs as the sample. The research instrument utilizes a Likert-scale questionnaire, which was tested for validity and reliability prior to use as a data collection tool for respondents. The pilot testing was conducted at the Ministry of Religious Affairs in Payakumbuh City, which was not included as part of the study sample. Validity testing included: (1) content validity, (2) construct validity through variable grid formulation, and (3) expert validity via expert judgment from two specialists. Data analysis employed inferential statistical analysis using Structural Equation Modeling (SEM) with IBM SPSS AMOS 26 software. The findings indicate a direct relationship between organizational culture (X1) and employee productivity (Y), evidenced by a path coefficient value of 0.230 and a critical ratio of 2.746. These values exceed the t-table value of 1.96, with a significance level of 0.006 (p < 0.05). Consequently, the alternative hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. The conclusion derived from the study is that organizational culture has a positive, direct, and significant influence on employee productivity at the Provincial Office of the Ministry of Religious Affairs in West Sumatra.